Autologous fascia lata graft for contour restoration and camouflage in tertiary rhinoplasty. - Karaaltin, Mehmet Veli; Batioglu-Karaaltin, Ayşegul; Orhan, Kadir Serkan; Demirel, Tayfun; Guldiken, Yahya (My University, 2012)
Tertiary rhinoplasty is a surgical procedure to correct nasal deformities that have been developed after prior unsuccessful surgeries. Such surgery requires complicated manipulations and tissue grafting for proper restoration. In the current study, we report the use of fascia lata graft combined with cartilage grafts for contour restoring and camouflage. Twenty-three patients who had severe nasal deformities were included, of whom 14 were men and 9 were women. Their ages ranged between 24 and 34 years (mean, 29 y). All patients were twice previously operated on by surgeons other than the authors. An informed consent was obtained from all patients. After harvesting the costal cartilage, the fascia lata graft (mean size, 2-3 cm) was uniformly harvested from the right lateral thigh. Application of the fascia lata and the cartilage graft was achieved through the open rhinoplasty incision. The fascia lata was applied over the cartilage in the dorsal region in 20 patients (86.9%), applied over the reconstructed alar and dome area in the nasal tip in 8 patients (34.7%), and applied over both areas simultaneously in 4 patients (17.3%). Postoperative follow-up was between 14 and 35 months (mean, 24.5 mo); clinical evaluation, photographic documentation, and a questionnaire form related to donor-site morbidity and patient satisfaction were applied after 12 months of the follow-up period. Results showed that all patients had an improved aesthetic result, and no apparent irregularities were observed in the integument of the aesthetic lines. No complications or no requirement for revision surgery was observed later on. In conclusion, refinements of the nasal dorsum and the nasal tip in tertiary rhinoplasty are indeed important and difficult to be managed. Placing the fascia lata over the applied cartilage grafts provide a good cover that conceals the possible irregularities or distortions that may appear in the late postoperative period.